Effect of suction on flow characteristics and sediment transport in closed-conduit flows - Cao, Deping (2015)
This study presents experimental studies on suction effects on sediment transport and flow characteristics such as velocity profile, turbulence and shear stress distribution, etc. The results show that the bedload transport rate increases with suction rate (with a constant undisturbed oncoming flow rate, Q0). A conceptual model with consideration of the near-bed vertical and horizontal forces is presented. Particle Image Velocimetry (PIV) measurement of the flow field shows that the flow characteristics in the near-bed region changes significantly in the presence of suction, i.e., the near-bed velocity increases significantly and deviates from traditional log-law but fits the modified law very well. In addition, the shear stress first increases before marginally decreasing with suction intensity, Is (= Vs/U0, where Vs and U0 are the suction velocity and mean streamwise velocity, respectivley). Consequently, a turning point at Is = 2.32% is noticed and a possible explanation is given. The experimental results also show that the suction zone length, like suction intensity in the form of Is, can influence the sediment transport rate. Combining the effect of Is and suction zone length, the study shows that suction intensity in the form of Qs/Q0 (Qs is the suction flow rate) is a superior variable to use in the analysis of sediment transport rate. Moreover, PIV measurement of the velocity profile shows that the streamwise velocity at the bed level increases with increasing Vs/U0 at fixed suction zone length and also with increasing suction zone length at fixed Vs/U0, which is used to explain how the suction zone length affects the sediment transport rate.